Macro Fundamental Analysis, Capital Structure on Financial Performance with Ownership Structure and Profit Management as Intervening Variables - Devi Nadia Agustina; Hwihanus (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
This study aims to analyze the effect of Macro Fundamentals and Capital Structure on Financial Performance with Ownership Structure and Earnings Management as intervening variables in primary consumer goods sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2023. The study used a quantitative approach with a simple random sampling technique of six companies, and data processing was carried out through the Structural Equation Modeling Partial Least Square (SEM-PLS) method using the SmartPLS 4 application. The results showed that Macro Fundamentals have a significant effect on Earnings Management and Ownership Structure, but not significant on Financial Performance. Ownership Structure has a significant effect on Financial Performance, while Earnings Management, Capital Structure, and their relationship with intervening variables show no significant effect. The findings indicate that macroeconomic conditions and ownership structure play an important role in influencing corporate financial performance, while capital structure and earnings management practices are not strong enough to have a direct impact.